Orange Peeling Technologies - de Arruda, Maria C.; Jacomino, Angelo P.; Pinheiro, Ana L.; Iuamoto, Marcia Y. (Recent Patents on Food, Nutrition & Agriculture, 2009)
Consumer demand for ready-to-eat products has stimulated the development of peeling techniques to prepare fresh-cut fruit and vegetables. The total peeling of oranges, that is, the removal of flavedo and albedo is difficult due to the adherence of the albedo to the segment membrane. Therefore, treatments which make peeling easier have been studied. This review comprehends patents and publications about orange peeling.
Keywords: Orange